Incidence rate of Soil Tranmitted Helminths Among Elementary School Students living in Coastal Areal of North Sulawesi - Indra Elisabet Lalangpuling; Kevin Giovani Pascoal; Sabrina Prisscilya Magdalena Pinontoan; Suwarja Suwarja; Meildy Esthevanus Pascoal (Universitas Aisyah Pringsewu, 2023)
The impact of helminthiasis if it occurs in children can result in a decrease in the health, nutrition, intelligence and productivity; It is also closely related to healthy living behavior or personal hygiene behaviours. This study aims to see the relationship between helminthiasis infection with nutritional status and personal hygiene behaviours in Tiwoho Elementary School students, Wori District, North Minahasa Regency. It was an observational study with cross-sectional design. This type of research is an observational study with a cross-sectional design. The total population is 69 students at SD Inpres Tiwoho. The sampling technique used was purposive sampling, where the stool samples were taken from students who had met the criteria, the samples used were 49 respondents. The results obtained from 49 students found that 6 students had worm infections with Ascaris lumbricoides species, 3 students Hookworm and 1 student Trichuris trichiura. There was no relationship between helminth infections and nutritional status and in personal hygiene behaviours there was a relationship between helminth infections with the habit of washing hands with soap before and after eating, cutting finger and toe nails and the habit of using footwear out of the house. Abstrak: Dampak kecacingan jika terjadi pada anak-anak dapat mengakibatkan menurunnya kondisi kesehatan, gizi, kecerdasan dan produktifitas penderitanya; hal ini juga erat kaitannya dengan perilaku hidup sehat. Penelitian ini bertujuan untuk melihat adanya hubungan antara infeksi kecacingan dengan status gizi dan PHBS pada siswa SD Inpres Tiwoho Kecamatan Wori Kabupaten Minahasa Utara. Jenis Penelitian ini merupakan penelitian observasional dengan desain cross-sectional. Jumlah populasi sebanyak 69 siswa di SD Inpres Tiwoho. Teknik pengambilan sampel menggunakan Purposive Sampling, dimana sampel feses yang diambil yaitu pada siswa yang telah memenuhi kriteria inklusi, sampel yang digunakan sebanyak 49 responden. Hasil yang didapatkan dari 49 anak siswa ditemukan 6 orang siswa mengalami infeksi kecacingan dengan spesies Ascaris lumbricoides, Hookworm sebanyak 3 orang siswa dan Trichuris trichiura 1 orang siswa. Tidak didapatkan hubungan antara infeksi kecacingan dan status gizi dan pada PHBS didaptkan hubungan antara infeksi kecacingan dengan kebiasaan mencuci tangan dengan sabun sebelum dan sesudah makan, menggunting kuku jari tangan dan kaki dan kebiasaan menggunakan alas kaki keluar rumah.